Quantum black holes - Calmet, Xavier (SpringerBriefs in Physics, 2014)
Written by foremost experts, this short book gives a clear description of the physics of quantum black holes. The reader will learn about quantum black holes in four and higher dimensions, primordial black holes, the production of black holes in high energy particle collisions, Hawking radiation, black holes in models of low scale quantum gravity and quantum gravitational aspects of black holes.